1990
DOI: 10.1055/s-2008-1026393
|View full text |Cite
|
Sign up to set email alerts
|

Prognostische Bedeutung des Tumorzellnachweises im Knochenmark von Patientinnen mit Mammakarzinom

Abstract: In 95% of patients with primary breast cancer, the extent of metastases cannot be proven by conventional methods. Nevertheless, more than 50% of these patients have a relapse within five years. To improve the predictive value for recurrency, we examined bone marrow aspirates of 128 patients with primary breast cancer. Bone marrow aspirates from 2-6 sites of the skeleton (iliac crest and sternum) were taken as well as biopsies for histological examination. The immunohistochemical studies were carried out on int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1992
1992
2000
2000

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…The percentage of tumour cell-positive patients (38%) in this study is slightly higher than in our earlier publications (Harbeck et al, 1987;Untch et al, 1988) or the percentage reported by some other groups (Mansi et al, 1987;Schlimok et al, 1987;Porro et al, 1988;Ellis et al, 1989;Diel et al, 1990). One explanation might be an improved detection rate by using an antibody cocktail instead of a single monoclonal antibody.…”
Section: Discussioncontrasting
confidence: 68%
“…The percentage of tumour cell-positive patients (38%) in this study is slightly higher than in our earlier publications (Harbeck et al, 1987;Untch et al, 1988) or the percentage reported by some other groups (Mansi et al, 1987;Schlimok et al, 1987;Porro et al, 1988;Ellis et al, 1989;Diel et al, 1990). One explanation might be an improved detection rate by using an antibody cocktail instead of a single monoclonal antibody.…”
Section: Discussioncontrasting
confidence: 68%
“…In consequence micrometas tases and their prognostic impact was most extensively studied in breast cancer patients, where the skeleton represents the most common site of distant tumor relapses [1,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Depending on the method and the antibody applied the preva lence may be found as low as 16% as published by Salvadori et al and Porro et al [17,27] or Ellis et al [24] This methodological aspect may have remarkable influence on the prognostic impact of positive bone marrow findings.…”
Section: Micrometastases In Breast Cancermentioning
confidence: 99%